Nursing Entrepreneurship Development: Literature Review - Asih Purwandari Wahyoe Puspita; Dinda Castury; Tirta Adikusuma Suparto; Yanti Hermayanti; Dian Rahayuningsih (Indonesian Journal of Community Development, 2021)
Background : Entrepreneurship in nursing has enormous and promising opportunities for a nurse. It includes palliative care / home care, nursing counseling, caregiver training, physiotherapy services and others. However, the development of entrepreneurship in nursing still faces several obstacles.Purpose The aim of this study was to explore the development of entrepreneurship in nursing.Method The method used in this study was literature review. Several data bases including Google schoolar, Garuda, National Library, DOAJ, PubMed, Sciencedirect, and Proquest were used. Keywords were chosenin accordance with MESH (Medical Subject Heading), including “kewirausahaan keperawatan”, “hambatan kewirausahaan keperawatan”,"mahasiswa keperawatan", "nursing entrepreneurship", "nursing entrepreneurial", "barrier of nursing entrepreneur", "opportunities of nursing entrepreneur”, and “nursing student” in April 2020. Based on the search results there were 4 national and 4 international articles related to the topic and match the inclusion and exclusion criteria. Findings Findings from 8 articles indicated that obstacles faced by entrepreneur nurses were more due to a lack of entrepreneurial knowledge, experience, and skills. There are several ways to overcome obstacles that occur in nursing entrepreneurship, namely: increasing entrepreneurial knowledge and experience, identifying opportunities via internet or social media, and always interacting among fellow entrepreneurs, patients and the community to find opportunities that have never been found before. The solution to develop nursing entrepreneurship is to increase the interest, knowledge, skills, training and experience of nursing entrepreneurs. This research is expected to be used as an evaluation of entrepreneurship learning and nursing entrepreneurship development programs.Conclusion In conclusion, the development of nursing entrepreneurship is still facing some obstacles that need to be overcome. The main key lies in increasing knowledge, interests and skills through entrepreneurial training and education.